2019
DOI: 10.1038/s41598-019-51178-w
|View full text |Cite
|
Sign up to set email alerts
|

Acetic acid: a cost-effective agent for mitigation of seawater-induced salt toxicity in mung bean

Abstract: The current study sought the effective mitigation measure of seawater-induced damage to mung bean plants by exploring the potential roles of acetic acid (AA). Principal component analysis (PCA) revealed that foliar application of AA under control conditions improved mung bean growth, which was interlinked to enhanced levels of photosynthetic rate and pigments, improved water status and increased uptake of K+, in comparison with water-sprayed control. Mung bean plants exposed to salinity exhibited reduced growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 74 publications
9
85
0
Order By: Relevance
“…This growth reduction eventually contributed to the significant yield loss of faba bean plants (Table 1). Similar findings were also reported in other legumes like Vigna radiata [13], Cicer arietinum [57], Lupinus albus [58], and Vicia faba [59] under saltstress condition. On the other hand, foliar applications of IAA resuscitated the growth performance of salt-stressed faba bean plants as shown by improved morphological at-…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This growth reduction eventually contributed to the significant yield loss of faba bean plants (Table 1). Similar findings were also reported in other legumes like Vigna radiata [13], Cicer arietinum [57], Lupinus albus [58], and Vicia faba [59] under saltstress condition. On the other hand, foliar applications of IAA resuscitated the growth performance of salt-stressed faba bean plants as shown by improved morphological at-…”
Section: Discussionsupporting
confidence: 89%
“…Various morpho-physiological and biochemical alterations emerge due to the ionic misbalance in plants, especially at early growth stages [12]. Salinity-induced water insufficiency and nutrient such as Ca 2+ , K + , Fe 2+ , and Zn 2+ deficiency within plants leads to photosynthesis disruption and oxidative stress [13]. Overall, salinity causes the reduction of leaf area, stomatal conductance, and chlorophyll levels in the plants [14] and promotes the generation of reactive oxygen species (ROS) [15].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, lower H 2 O 2 contents in drought-treated EX plants were observed (Figure 4b), which might be attributed to the higher CAT activities detected in the EX lines in comparison with WT plants under drought (Figure 4c). As SOD provide the first layer of antioxidant defense by dismutating superoxide radicals, the observation of enhanced SOD activities in the EX lines, when compared with that of WT plants, suggests the more pronounced protection of the EX lines from oxidative stress (Figure 4c) [85,87,88]. Furthermore, the higher degree of induction in CSD1 and CAT2 expression under dehydration conditions in the GmNAC109 -EX lines compared with that of WT indicates a positive relationship between the enzyme activities and gene expression levels under water deficit conditions (Figure 4c,d).…”
Section: Discussionmentioning
confidence: 99%
“…Application of exogenous phytohormones including CK has been proven as a promising sight in the alleviation of the adverse effects of salt toxicity in several vegetables and crops, such as brinjal (Solanum melongena Mill. ), soybean (Glycine max L.), mung bean (Cucumis sativus L.), rice (Oryza sativa L.) and maize (Zea mays L.) (Hadiarto and Tran, 2011;Javid et al, 2011a;Wu et al, 2014;Fahad et al, 2015;Tahjib-Ul-Arif et al, 2018b;Akram et al, 2019;Rahman et al, 2019). An important synthetic CK, BA has been recognized as the potential stress-mitigating phytohormones to the scientific community.…”
Section: Discussionmentioning
confidence: 99%